2013
DOI: 10.1128/mcb.01676-12
|View full text |Cite|
|
Sign up to set email alerts
|

Lamin A/C Depletion Enhances DNA Damage-Induced Stalled Replication Fork Arrest

Abstract: hThe human LMNA gene encodes the essential nuclear envelope proteins lamin A and C (lamin A/C). Mutations in LMNA result in altered nuclear morphology, but how this impacts the mechanisms that maintain genomic stability is unclear. Here, we report that lamin A/C-deficient cells have a normal response to ionizing radiation but are sensitive to agents that cause interstrand cross-links (ICLs) or replication stress. In response to treatment with ICL agents (cisplatin, camptothecin, and mitomycin), lamin A/C-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 50 publications
5
93
1
3
Order By: Relevance
“…Other studies have also implicated LA/C in the regulation of DNA synthesis. Recently, LA and LC were shown to play a significant role in the restart of replication forks following replicative stress and the recruitment of DNA repair complexes, but a direct interaction between LA/C and newly replicating chromatin was not demonstrated (5). We found that LA/C interacted directly with newly replicated DNA at multiple origins of replication, in contrast to LB1, which interacted only weakly with a minority of origins.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Other studies have also implicated LA/C in the regulation of DNA synthesis. Recently, LA and LC were shown to play a significant role in the restart of replication forks following replicative stress and the recruitment of DNA repair complexes, but a direct interaction between LA/C and newly replicating chromatin was not demonstrated (5). We found that LA/C interacted directly with newly replicated DNA at multiple origins of replication, in contrast to LB1, which interacted only weakly with a minority of origins.…”
Section: Discussionmentioning
confidence: 41%
“…2A), suggesting that most origins of replication are affected by the reduction of LB1 levels. Several studies have suggested that lamins can interact with sites of replication to affect the efficiency of replication; however, a direct biochemical interaction of lamins with sites of replication has not been demonstrated (5,23,33). In order to determine if the LB1-dependent decrease in DNA replication was due to a direct interaction of lamins with newly replicating DNA, we performed the BrdU ChIP procedure with nonsilenced cells followed by immunoblotting of the precipitated proteins for the presence of replication factors and lamins.…”
Section: ϫ3mentioning
confidence: 99%
See 1 more Smart Citation
“…A nucleoplasmic population of lamin A was reported to colocalize within chromatin foci that contain the replication proteins PCNA and DNA polymerase ␦; these foci are believed to represent sites of DNA replication in early S phase (5,6). Interestingly, lamin A/C deficiency enhances replication stress in cells treated with interstrand cross-linking agents, suggesting a role for lamin A/C in the recovery of stalled replication forks (53). Unprocessed prelamin A likely interferes with DNA replication by sequestering replication and repair factors (9,39,54).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of down-regulated protein, programmed cell death protein 6 (PDCD6), also called apoptosislinked gene 2 protein (ALG2), functions as calciumbinding protein required for T cell receptor-, Fas-, and glucocorticoid-induced cell death (Suzuki et al 2012;Yoon et al 2012). Besides their multifunction, four proteins, ATP-dependent RNA helicase DDX39A, complement component 1 Q subcomponent-binding protein (SF2p32), Lamin-A/C, and far upstream element-binding Protein 2 are involved in pre-mRNA splicing or as splicing factors to play an important role in DNA damage and repair (Dittmer and Misteli 2011;Filippov et al 2007;Marengo and Wassarman 2008;Singh et al 2013). Replication factor C (RFC) subunit 5 is down regulated, suggesting that RFC and Pol d may be synergistically involved in DNA repair events on lagging or leading strand with their altered functions by the down-regulation of their smallest subunits.…”
Section: Discussionmentioning
confidence: 99%